Aspek-aspek Pragmatik pada Percakapan dalam Dialog pada Novel Jepang dan Novel Terjemahannya - Kun Permatasari (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
Conversations in a dialogue generally contain meanings and expressions based on the culture that exists in the spoken situation. The conversation itself contains a pragmatic aspect based on the culture. If a conversation occurs in a novel, it will follow the cultural rules based on the author, so that the pragmatic aspects that occur are based on the speech situation in the conversational culture. If the conversation is translated into a different language, of course, the cultural rules and pragmatic elements will also change, according to the culture and background of the translator. Therefore, in seeking pragmatic equivalence in a conversation in two different languages, it is related to the cultural situation of their respective languages. This study aims to describe pragmatic aspects of conversation in dialogue in translated novels and original novels in Japanese, which include: speech acts, implicatures, and maxims. This research uses a qualitative approach with content analysis methods in the realm of pragmatics, namely conversations in dialogues in novels from both languages. Furthermore, the results obtained that there are equivalences and deviations in the pragmatic aspects of the conversation in the novel, namely, equivalence and deviations in speech acts, equivalence and deviations in implicatures, and equivalence and deviations in the types of maxims. Based on the results of the study, it can be concluded that the equivalence and deviation of pragmatic aspects occur in 5 types of speech acts, 2 types of implicatures and 4 types of maxims.